HE EFFECTIVENESS OF ROLE-PLAY TECHNIQUE TO IMPROVE STUDENTâS SELF-ESTEEM - Nuraini, nuraini (Jurnal Konselor, 2015)
The study aims to examine the effectiveness of role-play techniques in improving students self-esteem. The research method used a quasi experimental research with nonequivalent pretest-posttest control group design. Data was collected using a questionnaire of self-esteem.Â  The participants of study were students of class 10th total of 14 participants (11 male students and 3 female students) in each experimental and control group with simple random sampling technique. The results are: (1) studentâs self-esteem is in moderate category; (2) an intervention program of role-play techniques focused to improve studentâs self-esteem who are in the low category and maintain other aspects of self-esteem; and (3) group guidance program through the use of role-play techniques is specifically effective to improving students self-esteem, except the indicator There is participation in activities in the neighborhood in the Aspects of Significance. The recommendations are for school counselor, principals, and further research.Â Keywords: Effectiveness, Role-Play Technique, Self-Esteem